1999
DOI: 10.1136/jnnp.66.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Motor root conduction in neuralgic amyotrophy: evidence of proximal conduction block

Abstract: Objective-To determine the presence and role of proximal conduction block in neuralgic amyotrophy. Methods-Percutaneous electrical stimulation of cervical roots and brachial plexus was employed in eight patients with neuralgic amyotrophy. Root to Erb's point compound muscle action potential amplitude ratios for abductor digiti minimi, extensor digitorum communis, biceps, and deltoid muscles were compared with results obtained from 10 healthy controls. Results-Conduction block in the nerve to one muscle was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Although two electrophysiologic studies have shown that the lesions in this syndrome can be very proximal, it has not been possible to distinguish whether the nerve lesions are in individual nerves or in selective fascicles within nerve roots or the brachial plexus. 32,35 Although the latter has long been suggested by experienced clinicians, 11,50 the precise answer remains unclear.…”
Section: Acute Brachial Plexus Neuropathymentioning
confidence: 97%
“…Although two electrophysiologic studies have shown that the lesions in this syndrome can be very proximal, it has not been possible to distinguish whether the nerve lesions are in individual nerves or in selective fascicles within nerve roots or the brachial plexus. 32,35 Although the latter has long been suggested by experienced clinicians, 11,50 the precise answer remains unclear.…”
Section: Acute Brachial Plexus Neuropathymentioning
confidence: 97%
“…In addition, selective involvement of muscles supplied by the anterior interosseous nerve has long been recognised [15]. Electromyography (EMG) and nerve conduction studies have mainly suggested a process of axonal degeneration at the brachial plexus [4] although recent studies have reported motor conduction block across the brachial plexus [1,11]. Motor conduction block in nerves distal to the brachial plexus has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases of neuralgic amyotrophy evidence of proximal motor conduction block has been provided [2,4] . Watson et al [4] showed a partial conduction block between the cervical spinal roots and axilla in 2 patients 6-8 weeks after onset.…”
Section: Discussionmentioning
confidence: 99%
“…On follow-up examinations on day 54 his moDear Sir, Neuralgic amyotrophy is a well-established clinical syndrome characterized by an acute onset of shoulder and arm pain followed by muscular weakness, wasting and variable sensory loss [1] . Most neurophysiological studies have reported features of axonal degeneration [2] , reflecting terminal pathological results rather than the underlying process. We report a patient with neuralgic amyotrophy who was examined within a week after pain onset.…”
mentioning
confidence: 99%
See 1 more Smart Citation